The role of the mosque as a medium of da'wah in building religious tolerance in the community: An analysis of Kampung Toleransi - Ilyasa, Faisal Fauzan; Fakhruddin, Agus; Faqihuddin, Achmad; Ramdan, Muhammad Ramdan Mubarok; Muflih, Abdillah (Islamic Communication Journal, 2024)
Tolerance is a serious discussion in Indonesia. Establishing Kampung Toleransi (Tolerance Village) is among the government's efforts to create harmony between religious communities. This research aims to examine the role of mosques in building tolerance in society in an area known as the Village of Tolerance. Data for this research was obtained through in-depth interviews with community members and religious figures involved in religious activities in the Tolerance Village. Analysis was carried out using NVivo12 software to enable collection, organization, and a deeper understanding of this tolerance practice. The results of this research reveal diverse tolerance practices in the religious context of the Village of Tolerance. Social, cultural, and religious factors are essential in shaping tolerance practices. Nonetheless, the village stands out for its ability to encourage interfaith dialogue, cooperation, and respect for differences. The results of this research can provide a deeper view of how society can achieve greater tolerance in religious contexts through interfaith cooperation and dialogue. This research has the potential to make an essential contribution to understanding the practice of tolerance in religiously and culturally diverse societies. ***** Toleransi menjadi pembahasan yang serius di Indonesia. Di antara upaya pemerintah dalam mewujudkan kerukunan antarumat beragama yaitu dengan membentuk Kampung Toleransi. Penelitian ini bertujuan untuk mengkaji peran masjid dalam membangun toleransi di masyarakat pada sebuah daerah yang dikenal dengan sebutan Kampung Toleransi. Data untuk penelitian ini diperoleh melalui wawancara mendalam dengan anggota masyarakat dan tokoh agama yang terlibat dalam kegiatan keagamaan di Kampung Toleransi. Analisis dilakukan menggunakan perangkat lunak NVivo12 agar pengumpulan, pengorganisasian, dan pemahaman yang lebih mendalam tentang praktik toleransi ini. Hasil penelitian ini mengungkap praktik toleransi yang beragam dalam konteks keagamaan di Kampung Toleransi. Faktor-faktor sosial, budaya, dan agama memainkan peran penting dalam membentuk praktik-praktik toleransi. Meskipun demikian, kampung ini menonjol karena kemampuannya dalam mendorong dialog antaragama, kerjasama, dan penghormatan terhadap perbedaan. Hasil penelitian ini dapat memberikan pandangan yang lebih dalam tentang bagaimana masyarakat dapat mencapai toleransi yang lebih baik dalam konteks agama melalui kerja sama dan dialog antaragama. Penelitian ini berpotensi memberikan kontribusi penting dalam memahami praktik toleransi dalam masyarakat yang beragam secara agama dan budaya.